2016
DOI: 10.9734/bjmcs/2016/29698
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-plane Equilibrium Points in the Photogravitational Restricted Four-body Problem with Oblateness

Abstract: The restricted four-body problem consists of an infinitesimal particle which is moving under the Newtonian gravitational attraction of three massive bodies, called primaries. The three bodies are moving in circles around their common centre of mass fixed at the origin of the coordinate system, according to the solution of Lagrange, where they are always at the vertices of an equilateral triangle. The fourth body does not affect the motion of the primaries. We consider that the primary body P 1 is dominant and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
3
6
0
Order By: Relevance
“…As evidenced in Tables 6-9, for each set of values, there exist at least one complex root with positive real part and hence in Lyapunov sense, the stability of the out-of-plane equilibrium points are unstable. This result affirmed with that of [1,4,10,11,12,14,15].…”
Section: Numerical Applicationssupporting
confidence: 80%
See 2 more Smart Citations
“…As evidenced in Tables 6-9, for each set of values, there exist at least one complex root with positive real part and hence in Lyapunov sense, the stability of the out-of-plane equilibrium points are unstable. This result affirmed with that of [1,4,10,11,12,14,15].…”
Section: Numerical Applicationssupporting
confidence: 80%
“…These points lie in the −plane symmetrically with respect to the − along the curve almost directly above and below the center of each oblate primary. These points are denoted by 6,7 [1,10,13,14,15]. Das et al [14] observed that, in the photo-gravitational circular restricted three-body problem, the out-of-plane equilibrium points are of a passive micro size particle when their stability in the field of radiating binary systems are considered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Papadouris et al [9,10] studied the existence, the location, stability and periodic orbits of the equilibrium points on and out of the orbital plane in the photo-gravitational R4BP. Singh and Vincent [11,12] studied equilibrium points in CR4BP with the effect of solar radiation pressure and also not considered the albedo effect.…”
Section: Introductionmentioning
confidence: 99%
“…Shrivastava et al in [46] evaluated the equilibrium points in the Robes restricted problem of three-bodies with effect of perturbations in the coriolis and centrifugal forces. Singh et al in [50][51][52][53][54][55][56][57][58][59] studied the restricted problem of three-bodies and four-bodies in circular and elliptic cases with different perturbations. Khanna et al in [29,30] explored the existence and stability of libration points in the restricted three-body problem when the smaller primary is a triaxial rigid body and the bigger one an oblate spheroid and observed that there are five libration points in which three collinear libration points are unstable and two triangular points are stable for the particular mass parameter.…”
Section: Introductionmentioning
confidence: 99%